Lithium as an Alternative Option in Graves Thyrotoxicosis - Ishita Prakash; Eric Sixtus Nylen; Sabyasachi Sen (Case Reports in Endocrinology)
A 67-year-old woman was admitted with signs and symptoms of Graves thyrotoxicosis. Biochemistry results were as follows: TSH was undetectable; FT4 was >6.99 ng/dL (0.7–1.8); FT3 was 18 pg/mL (3–5); TSI was 658% (0–139). Thyroid uptake and scan showed diffusely increased tracer uptake in the thyroid gland. The patient was started on methimazole 40 mg BID, but her LFTs elevated precipitously with features of fulminant hepatitis. Methimazole was determined to be the cause and was stopped. After weighing pros and cons, lithium was initiated to treat her persistent thyrotoxicosis. Lithium 300 mg was given daily with a goal to maintain between 0.4 and 0.6. High dose Hydrocortisone and propranolol were also administered concomitantly. Free thyroid hormone levels decreased and the patient reached a biochemical and clinical euthyroid state in about 8 days. Though definitive RAI was planned, the patient has been maintained on lithium for more than a month to control her hyperthyroidism. Trial removal of lithium results in reemergence of thyrotoxicosis within 24 hours. Patient was maintained on low dose lithium treatment with lithium level just below therapeutic range which was sufficient to maintain euthyroid state for more than a month. There were no signs of lithium toxicity within this time period. Conclusion. Lithium has a unique physiologic profile and can be used to treat thyrotoxicosis when thionamides cannot be used while awaiting elective radioablation. Lithium levels need to be monitored; however, levels even at subtherapeutic range may be sufficient to treat thyrotoxicosis.